Lighting for SDG#3 Wellness and #12 Responsible Production and Consumption via ISO 14068 - Ching, Shirley Yeung Mo; Lee, Bernard (Journal of Ecohumanism, 2025)
Based on Green Curriculum Guidance of UNESCO, 2024 “this Guidance includes numerous references to curricula developed by ministries, CSOs and inter-governmental organizations. Greening education encompasses not only knowledge and intellectual skills acquisition, but also socioemotional dispositions, such as a motivation to ‘make a difference’ and skills. It is time to explore transformative ways of educating lighting issues for the hospitality industry with a pilot of lighting in sustainable hotel room to engage industry practitioners, management and graduates in the hospitality discipline for enhancing IMM and UNPRI framework measurements. This paper is to explore the concepts and expected skills development of the GEEP (Green Entrepreneurial Education Project) - an action-based experiential approach for talent development and case study with Hotels in Beijing, China on lighting design. The feasible actionable steps aligned with the SDGs, particularly SDG3 (Wellness), SDG 12 (Responsible Consumption and Production), SDG 13 (Climate Action), SDG 8 (Decent Work and Economic Growth), SDG 9 Innovations, and SDG 17 (Partnerships for the Goals). It is suggested to implement ISO 14068-2023 Climate Change Management System for Transition to Net Zero in design of lighting in hotels to reinforce responsible management in the hotel common areas and hotel rooms with wellness.